The Effect of Environmental and Social Governance on Company Profitability Levels - Azkiya, Satria Tsani; Azmi, Ika Nur; Kurniawan, Rudy (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The aim of this research is to find out how Environmental, Social, and Governance (ESG) Disclosure awareness is related to profitability in Food and Beverage (FnB) sector companies listed on the Indonesia Stock Exchange. This research includes traditional assumption testing, hypothesis evaluation, and descriptive statistical analysis. The test consists of multiple linear regression analysis, simultaneous f test, coefficient of determination test (R2), and partial t test. The preliminary findings suggest that there is no meaningful influence on the dependent variable from ESG disclosure because the significance level of the ESG variable is above 0.05. Conversely, the ENV, SOC, and GOV factors possess a substantial impact regarding the dependent variable as their significance level is below 0.05. The research emphasizes the importance of the link between ESG disclosure and company profitability within the realm of corporate social responsibility, indicating that ESG disclosure could have a positive influence on company profitability through improving the company’s reputation and boosting customer loyalty.